A Systematic and Meta-Analytical Review of Acceptance and Commitment Therapy for PTSD - Sana, Rehman; Siti Raudzah, Ghazali; Ask, Elklit (Taylor & Francis Group, LLC, 2025)
Approximately 14% of individuals develop PTSD symptoms in response to trauma. Existing literature provides substantial evidence supporting Acceptance and Commitment Therapy (ACT) in enhancing psychological flexibility and reducing PTSD symptoms. This study aimed to investigate the efficacy of ACT in managing PTSD symptoms. The PRISMA flowchart was used to guide the selection of relevant studies. A comprehensive meta-analysis was conducted to determine the effect size of ACT’s efficacy. A total of 25 studies were included in the systematic review, while 20 studies were included in meta-analysis. The quality of the selected studies was independently assessed by two reviewers using a quality rating scale (Yates et al., 2005). Meta-analytic findings indicated a mean effect size of 1.274 with a 95% confidence interval of 0.906 to 1.643, reflecting a large treatment effect. However, the narrative synthesis revealed that results across studies were not directly comparable due to heterogeneous study characteristics. This study highlights the strong potential of ACT as an effective intervention for PTSD, particularly in the context of natural and human-made disasters or traumatic incidents. Despite variability across studies, the overall evidence supports ACT’s use in trauma-informed care, warranting further investigation through high-quality, standardized trials.